Avaliação de compósitos de polipropileno virgem e polietileno reciclado reforçados com fibras de sisal para aplicações em peças automotivas - Amorim, Laudenor (2018)
The development of more resistant and inexpensive materials was important for the emergence of composites, materials that are the result of the mixing of two or more distinct components with improved properties. The use of vegetable fibers as reinforcing filler for polymer matrix composites, help to reduce the cost as well as maintaining product quality. The ease in sisal cultivation was of interest for its use in the production of composites with virgin polypropylene (PP) and recycled polyethylene (RPE) matrices. The fibers were divided into two groups: mercerized and acetylated. In order to evaluate the use in automotive parts, such as bumpers, fuel tanks, and internal coatings, were produced PP and REP composites reinforced with randomly oriented fibers in the percentages 0% wt., 5% wt., 10% wt. and 15% wt.. For the chemical treatment of fibers, were used 2% NaOH solution, and acetylation with acetic acid and acetic anhydride in the ratio (1:1,5). The characterization of the fibers and composites was done using Infrared (FTIR), UV-Vis by Diffuse Reflectance (UVDR) and Scanning Electron Microscopy (SEM) techniques to analyze fiber-matrix adhesion without damaging the fibers. The mapping of the chemical composition of the fibers and the polymers was obtained with the aid of the Energy-dispersive X-Ray Spectroscopy (EDS) technique. The mechanical evaluation was performed by means of hardness, impact and tensile tests. In order to guarantee the reliability of the results of the tensile test, it was used the Weibull Statistical Analysis, which provided the average value of the maximum tension supported by the test specimens. The main changes observed with the chemical treatments were the removal of impurities and the smaller amount of water absorbed in the acetylated fibers, which were better incorporated in the polymer matrices. The FTIR spectra presented the functional groups, UVDR made it possible to estimate the band energy values and the insulating character of the materials. The main fracture regions between the fiber and matrix can be observed through the surface analysis of the composites. Thus, PP composites were hard and fragile, while RPE composites were soft and tenacious. From the SEM images, it was noticed that the highest percentage of fibers used was not well incorporated in the matrices, which was confirmed through the other techniques used.